THE INFLUENCE OF SELF-CONTROL ON PROCRASTINATION OF EDUCATION PERSONNEL AND LECTURERS BASED ON GENDER - Handayani, Selvian; Alif, Muh. Ikhsan; Fitria, Irma; Hidayat, Muhammad Afdelpiero; Syabina, Masayu Sitti Nur (Idaarah: Jurnal Manajemen Pendidikan, 2024)
The role of academics in achieving the goal of educating the nation is very important, as demonstrated by lecturers and academic staff. Effective time management is essential, yet procrastination is still common, often putting off tasks such as preparing teaching materials, grading, and completing research. Procrastination, a complex issue involving self-control, negatively impacts work quality and academic productivity. This study aims to analyses the influence of self-control on academic procrastination among lecturers and academic staff at Kalimantan Institute of Technology, focusing on gender-based patterns. Using purposive sampling, data was collected through questionnaires and analyzed using Structural Equation Modeling (SEM-PLS). Findings showed a significant negative relationship between self-control and procrastination, with a stronger effect among male academics. This suggests that higher self-control correlates with lower procrastination tendencies. These results underscore the importance of self-control in managing academic responsibilities and highlight the need for targeted interventions to improve time management and self-regulation. It is recommended that educational institutions develop training programs that focus on improving self-control, especially tailored to male academics, to reduce procrastination and improve overall productivity.